4 Studying contrast administration in the fontan circulation using mr time resolved angiography. (15th May 2019) - Duerden, Laura; Hamilton, Mark
Abstract : Introduction: When patients with Fontan circulation require CT imaging, there are significant challenges in achieving adequate contrast opacification due to altered anatomical connections. This study uses MR time resolved angiography to examine contrast circulation in a cohort of patients with Fontan circulation to optimise contrast injection protocol for CT. Methods: Time to peak signal intensity was recorded using regions of interest on the aorta, the pulmonary arteries and the Fontan conduit on MR TWIST angiography images. Patients were stratified into groups according to ejection fraction, global longitudinal strain, indexed stroke volume and cardiac index to examine the effect on time to peak signal intensity. Results: 35 patients were included in the study. Mean time to peak contrast enhancement was 31s in the thoracic aorta, 46s in the right pulmonary artery, 41s in the left pulmonary artery and 55s in the Fontan conduit. Cardiac performance shows little relationship to peak vascular enhancement whether measured by ejection fraction, global longitudinal strain, stroke volume index and cardiac index. Discussion: This MRI data suggest that optimal timing for a single phase examination to show all the major vessels is around 55 seconds following start of contrast injection. In TWIST MR angiography the IV bolus is 4-5 seconds long. A longer bolus is required for CTA, around 20s, suggesting an additional delay will be required. Further work will be done to see is a single phase examination at 70 seconds is an ideal initial strategy, with targeted further imaging if unsuccessful.